2009
DOI: 10.4103/0972-2327.58282
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid in multiple sclerosis

Abstract: Background:Technological advances have made it possible to examine the human cerebrospinal fluid (CSF) in a manner that was previously impossible. CSF provides a window into the changes that occur in the central nervous system (CNS) in health and disease. Through analysis of the CSF, we discern indirectly the state of health of the CNS, and correctly or incorrectly, draw conclusions regarding mechanisms of CNS injury and repair.Objective, Materials and Methods:To review the current state of knowledge of change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 47 publications
(52 reference statements)
0
17
0
1
Order By: Relevance
“…The key observation that led to the discovery of OCB dates to 1942, when Kabat described elevated gamma globulins in the CSF of MS patients. In 1959, Karcher, van Sande and Lowenthal reported that agar electrophoresis could differentiate CSF gamma-globulins from a patient with subacute sclerosing panencephalitis 4,5 . Since 1986, OCB detection in CSF has been routinely carried out using isoelectric focusing on agarose gel with immunoblotting.…”
Section: Discussionmentioning
confidence: 99%
“…The key observation that led to the discovery of OCB dates to 1942, when Kabat described elevated gamma globulins in the CSF of MS patients. In 1959, Karcher, van Sande and Lowenthal reported that agar electrophoresis could differentiate CSF gamma-globulins from a patient with subacute sclerosing panencephalitis 4,5 . Since 1986, OCB detection in CSF has been routinely carried out using isoelectric focusing on agarose gel with immunoblotting.…”
Section: Discussionmentioning
confidence: 99%
“…Th e main source of case identifi cation were hospital medical fi les, with relevant medical data routinely collected by neurologists at the Neuroimmunology and Neurogenetics Unit, Clinical Department of Neurology, Sestre milosrdnice University Hospital Centre in Zagreb, Croatia, during hospitalization. Relevant registry data included the following: age and gender; family history of MS; data on previous immunization: vaccination for morbillivirus (measles virus), parotitis virus (mumps) and rubella virus, hepatitis B virus (HBV), and other nonspecifi c vaccination; MS disease course (primary progressive MS (PPMS), remitting relapsing MS (RRMS), or secondary progressive MS (SPMS); Expanded Disability Status Scale (EDSS) score; cerebral magnetic resonance imaging (MRI) T2/FLAIR lesion load quantifi cation: moderate lesion load (0-9), signifi cant lesion load (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) and progressive lesion load (more than 20); cerebrospinal fl uid (CSF) examination: protein index for evaluation of intrathecal IgG synthesis, evaluation of the blood-brain-barrier permeability, presence of oligoclonal bands (OCBs); evaluation of polyspecifi c, intrathecal humoral immune response against viral agents including antibodies to measles, rubella and varicella zoster virus (MRZ) reaction (MRZR); and further CSF analysis for Borrelia burgdorferi, neurotropic viruses, and central nervous system (CNS) parasites. Lifestyle habits, smoking and alcohol consumption were also analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…OCBs are bands of oligoclonal immunoglobulins, mainly immunoglobulin G (IgG), which are separated based on differences in isoelectric points (Rammohan, 2009). The existence of these bands within the CSF, but not within the serum, is a strong indicator of intrathecal antibody synthesis and, interestingly, is found in nearly all patients with clinically definitive MS (Zeman et al, 1996).…”
Section: B Cells and Antibodiesmentioning
confidence: 99%